Adverse effects of new antiepileptic drugs - ONAT, FİLİZ (PROUS SCIENCE, SAU-THOMSON REUTERS, 2004)
Starting with phenobarbital in the 1900s, it took almost 70-80 years to introduce old-generation agents for the treatment of epilepsy. Then, in eleven years, nine more new antiepileptic drugs were added to the armamentarium. These drugs produce a nearly 40-50% decrease in seizure incidence in refractory patients, but few patients have been able to achieve complete freedom from seizures. So the search for more effective drugs with minimal adverse effect profiles will continue. Although the new antiepileptic drugs do not demonstrate a superior efficacy compared to the older ones, they do offer some advantages in terms of tolerability, fewer drug interactions and simpler pharmacokinetics. However, our knowledge concerning their safety profiles can not yet be considered adequate due to the relatively short time these drugs have been on the market and to the limited number of patients exposed to them. The fact that the serious side effects of felbamate and vigabatrine appeared late after marketing should be taken as an important lesson because it implies the potential for unknown side effects at any time during treatment. Antiepileptic drug treatment should begin with diagnosis of the seizure and epileptic syndrome, followed by selection of the drug most appropriate for treatment of the individual patient, and continued with monitoring of not only the seizures but the adverse effect profile as well. (C) 2004 Prous Science. All rights reserved.
Keywords: ADD-ON THERAPY; NONCONVULSIVE STATUS EPILEPTICUS; VISUAL-FIELD CONSTRICTION; ANGLE-CLOSURE GLAUCOMA; LONG-TERM USE; DOUBLE-BLIND; PARTIAL SEIZURES; CONTROLLED TRIAL; ADJUNCTIVE TREATMENT; ELDERLY-PATIENTS